Tindak Tutur dalam Film Assalamualaikum Calon Imam - Sri Puji Astuti (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
The purpose of this research is to describe the type and function of speech acts in the film of Asalamualaikum Calon Imamku.. The method of data collection in this study is the observation method, continued by the note taking technique. Then, the data was analyzed by using the theory of speech acts. Based on the result of the research was found five kinds of speech acts used in the film of Asalamualaikum Calon Imamku, namely representative speech acts, directive speech acts, expressive speech acts, commissive speech acts, and declarative speech acts. Representative speech acts found function to report, expect, acknowledge, and show. Directive speech acts found function to force, advise, prohibit, ask, order, beg, invite, and suggest. Expressive speech acts found function to criticize, judge, blame, warn, and praise. The commissive speech act found function to promise and state the capability. The declarative speech act found function to authorize.